Radiofrequency ablation for the treatment of gastric antral vascular ectasia - Dray, Xavier; Repici, Alessandro; Gonzalez, Pedro; Fristrup, Claus; Lecleire, Stéphane; Kantsevoy, Sergey; Wengrower, Dov; Elbe, Peter; Camus, Marine; Carlino, Alessandra; Pérez-Roldán, Francisco; Adar, Tomer; Marteau, Philippe (Endoscopy, 2014)
Background and study aims: The traditional endoscopic treatment for gastric antral vascular ectasia (GAVE) is argon plasma coagulation, but results are not always positive. Radiofrequency ablation (RFA) is a new endoscopic therapy that may be an attractive option for the treatment of GAVE. The aim of this study was to assess the efficacy and safety of RFA for the treatment of GAVE.Patients and methods: This was an open-label, retrospective, case series study. The main outcome measures were number of red blood cell (RBC) packs transfused (transfusion requirement) and hemoglobin concentrations (g/dL) in the 6 months prior to and after RFA. Success was defined as a decrease in transfusion requirement in the 6 months after RFA compared with before treatment.Results: A total of 24 patients underwent a mean of 1.8 ± 0.8 RFA sessions. No complications were reported. One patient was referred for additional argon plasma coagulation during follow-up. The mean number of RBC packs decreased in all 23 transfusion-dependent patients, from a mean of 10.6 ± 12.1 during the 6 months prior to RFA, to a mean of 2.5 ± 5.9 during the 6 months after RFA treatment (P < 0.001), and 15 patients (65.2 %) were weaned off transfusions completely. An increase in the hemoglobin concentration was reported in all patients after RFA (from 6.8 ± 1.4 g/dL to 9.8 ± 1.8 g/dL; P < 0.001).Conclusion: RFA for the treatment of GAVE seems feasible and safe, and significantly reduced the need for RBC transfusion and increased the hemoglobin level in this retrospective case series.